Immunohistochemistry is the method of choice in the differential diagnosis of neoplastic pleurisies of unknown etiology - O. V. Ivanov; V. N. Klimenko; V. I. Novik; G. V. Nikolaev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The study included 61 patients with exudative neoplastic pleurisy of unknown primary localization. All patients underwent immunocytochemical study of pleural exudate to determine the etiology of effusion. Immunocytochemistry of 55 patients (90 %) of 61 ones was effective. The reason of exudation was both primary tumors — lung cancer (22), pleural mesothelioma (4) and pleural metastases of tumors of other localization - cancers of ovaries (9), breast (4), kidney (3), uterine body (2) , malignant lymphoma (2), colon (2), pancreas (2), thyroid gland (2), stomach (1), prostate (1), vagina (1). Immunocytochemical study of pleural effusions is the method of choice for the differential diagnosis of neoplastic pleurisies of unknown etiology.